Study on the relationship between relieving energy crisis in myofascial trigger points with An-Pressing manipulation and AMPK/PGC-1α pathway activation - Kuang, Xiaoxia; Li, Wu; Jiang, Quanrui; Wei, Wei; Li, Tielang; Li, Jiangshan (Journal of acupuncture and tuina science, 2022)
Objective To explore the mechanism of An-Pressing manipulation in relieving energy crisis in chronic myofascial trigger points (MTrPs) by observing the effects of An-Pressing manipulation on adenosine triphosphate (ATP), adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK)/peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) pathway and mitochondrial ultrastructure of skeletal muscle cells in MTrPs rats. Methods Forty-eight male Sprague-Dawley rats were randomly divided into a blank group, a model group, a lidocaine group, and an An-Pressing manipulation group, with 12 rats in each group. The model group, lidocaine group and An-Pressing manipulation group were used to replicate the MTrPs rat model by blunt shock and centrifugal motion method. After modeling, the An-Pressing manipulation group was subjected to 7 times An-Pressing manipulation, once every other day; the lidocaine group was treated with 3 times of injection of lidocaine at the MTrPs, once every 6 d. The blank group and the model group were fed normally without intervention. After the intervention, local muscle tissue was taken to detect the content of ATP and the expression of AMPK, phosphorylated AMPK (phospho-AMPK), PGC-1α, and glucose transporter 4 (GluT4), and the ultrastructure of mitochondria was observed under an electron microscope. Results Compared with the blank group, the ATP content in the model group was decreased ( P <0.05), the protein expression levels of phospho-AMPK, PGC-1α, and GluT4 and the ratio of phospho-AMPK to AMPK were decreased ( P <0.05); under the electron microscope, the number of mitochondria decreased, and they were deformed, small in volume, and had deformed cristae. Compared with the model group, the ATP contents in the An-Pressing manipulation group and the lidocaine group were increased ( P <0.05), and the protein expression levels of phospho-AMPK, PGC-1α, and GluT4 and the ratio of phospho-AMPK to AMPK were increased ( P <0.05); under the electron microscope, the number of mitochondria increased, the shape and size of the mitochondria were basically normal, and the cristae could be seen. Compared with the lidocaine group, phospho-AMPK and the ratio of phospho-AMPK to AMPK in the An-Pressing manipulation group were increased ( P <0.05); under the electron microscope, the numbers of mitochondria were similar, and the shape and size of the mitochondria were basically normal without swelling, and the cristae could be observed. Conclusion An-Pressing manipulation can increase the ATP content in MTrPs tissue, improve the expression levels of PGC-1α and GluT4 proteins and the ratio of phospho-AMPK to AMPK; its mechanism may relate to the activation of AMPK/PGC-1α signaling pathway to promote the repair of mitochondrial damages.